Reaching near-theoretical strength by achieving quasi-homogenous surface dislocation nucleation in MgO particles. (May 2022) - Chen, Sijing; Liu, Fei; Liu, Boyu; Chen, Xiao; Ke, Xiaoxing; Zhang, Manchen; Tang, Xiaochang; Guan, Pengfei; Zhang, Ze; Shan, Zhiwei; Yu, Qian
Graphical abstract: Abstract: The structural stability of the ceramic nanoparticle (NP) is essential for its versatile applications in broad fields. Due to inevitable imperfections on the surfaces, the NP usually yields at a stress that is far below its theoretical strength. Here we propose an effective way to approach the theoretical strength of the NPs by simply homogenizing the primary imperfections. Electron beam irradiation is utilized to modify the original uneven surface and achieve surface nano-crystallization in MgO NPs, which leads to more homogeneous stress distribution intrinsically as proved by numerical simulations. As a result, quasi-homogeneous surface nucleation of dislocations occurs and raises the compressive strength to be three times higher than the as-received particles with the original surface. The near-theoretical strength gained here indicates that the imperfection in materials can be homogenized to optimize the properties to approach that of perfect crystals.